Mountains - Pettiford, Rebecca (Minneapolis, MN : Jump!, 2018)
Carefully leveled text and vibrant photographs introduce early readers to mountains.
Top of the world -- Building a mountain -- Mount Everest.
Includes index.
2.3
K-3
490L
Keywords: Mountains -- Juvenile literature; Landforms -- Juvenile literature; Everest, Mount (China and Nepal) -- Juvenile literature; Mountains; Landforms; Everest, Mount (China and Nepal)